A CULTURE REPRESENTED BY THE WORDS “WHITE AND WHITENING” ON HAND AND BODY LOTION PRODUCT’S LABEL - Suntiarko, Cindy Clarissa (LANTERN (Journal on English Language, Culture and Literature), 2016)
This research is about the words ‘white’ and ‘whitening’ that are found on the label of hand & body lotion product which represent a cultural product based on the study of Linguistic Anthropology. This research is purposely conducted as the writer notices that hand and body lotion product contains linguistic data manifesting Indonesian culture, particularly women. The purpose of the study is to reveal the culture of Indonesian women that is set by the hand and body lotion products’ producers by using the words ‘white’ and ‘whitening’ in the labels of hand and body lotion products. The writer used Open-ended Questionnaire from Creswell (2010:26) to collect the respondents’ answers. To collect the words ‘white’ and ‘whitening’, the writer used Note-Taking Technique from Creswell (2010:272) and Non-Participatory Observation Method from Liu and Maitlis (2010). To analyze the data, the writer used Theory of Culture as a System of Mediation by Duranti (1997:40-41). The writer found that the words ‘white’ and ‘whitening’ refer to a certain concept of what Indonesian women expect to be. The writer concludes that it is a condition that one characteristic of beauty shaped by the Indonesian women is having white or bright complexion.